Andrographis paniculata Ethanol Extract Alleviates High Glucose-induced Senescence of Human Umbilical Vein Endothelial Cells via the Regulation of mTOR and SIRT1 Pathways - Khatimah, Nurul Gusti; Arozal, Wawaimuli; Barinda, Agian Jeffilano; Antarianto, Radiana Dhewayani; Hardiany, Novi Silvia; Shimizu, Ippei; Fadhillah, Muhamad Rizqy (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Chronic exposure of high glucose (HG) in endothelial cell induces senescence which may contribute to the development and progression of age-related diseases including insulin resistance. Andrographis paniculata improves insulin resistance in recent in vitro and in vivo studies. Anti-inflammatory and antioxidant properties of A. paniculata may be the new therapeutic approach to inhibiting premature senescence. However, the senolytic effect of A. paniculata on endothelial cells has not been investigated comprehensively. This study was conducted to evaluate the effect of A. paniculata extract on HG-induced endothelial cell senescence and the underlying mechanisms.METHODS: Human umbilical vein endothelial cells (HUVECs) were treated with 33 mM HG and 7.5 μg/mL A. paniculata extract for 48 hours. The expressions of p16, p21, interleukin (IL)-6, IL-8, insulin receptor substrate (IRS)-1, mammalian target of rapamycin, and sirtuin 1 (SIRT1) were measured by performing real-time quantitative polymerase chain reaction (RT-qPCR). The senescence-associated-β-galactosidase (SA-β-gal) staining was performed to observe the positive-stained senescent cells, while the cell surface expression of IL-1α was examined with flow cytometry method.RESULTS: A. paniculata extract reversed senescence in HUVECs under HG conditions by reducing mRNA expressions of p16 and p21, the number of SA-β-gal-positive-stained cells, and the expression of IL-1α on cell surface, which decreased the activation of IL-6 and IL-8. In addition, A. paniculata extract decreased the mRNA expression of mTOR and increased the mRNA expressions of IRS-1 as well as SIRT1.CONCLUSION: A. paniculata extract ameliorated senescence and improved insulin sensitivity by regulating the mTOR, SIRT1, and IRS-1 mRNA expressions on HG-treated HUVECs.KEYWORDS: Andrographis paniculata, endothelial cell, senescence, high glucose, nutrient-sensing pathways